Theory of timber connections with slender dowel type fasteners. Issue 1 (1st January 2018) - Svensson, Staffan; Munch-Andersen, Jørgen
ABSTRACT: A theory on the lateral load-carrying capacity of timber connections with slender fasteners is presented. The base of the theory is the coupled mechanical phenomena acting in the connection, while the wood and the slender fastener deform and yield prior to failure. The objective is to derive a sufficient description of actions and responses which have determining influence on the load-carrying capacity of timber connections with slender fasteners. Model assumptions are discussed and made, but simplifications are left out. Even so, simple mathematical equations describing the lateral capacity are derived from mechanical equilibrium of the deformed fastener. The herein proposed theory is verified against tests. The tests were designed to vary the influence of isolated mechanical phenomenon as much as possible. The theory shows a very high accuracy and precision when predicting the load-carrying capacity of the tested connections.